Assessment of the Nutritional Quality and Fungal Contamination of Commercial Poultry Feed and Raw Materials Available in Gazipur and Mymensingh District of Bangladesh - Hossain, Md. Delowar; Haque, Arshadul; Hoque, S. A. Masudul; Ahmed, Shabbir; Islam, Md. Rashidul; Rahman, Md. Morshedur; Islam, Shilpi; Selim, Abu Sadeque (European Journal of Applied Sciences, 2023)
The study was conducted to evaluate the nutrient content and fungal contamination of commercial poultry feeds and raw materials available in Gazipur and Mymensingh districts of Bangladesh. A total of 67 commercial poultry feed (broiler and layer) and raw materials were collected from different poultry farms, dealers and shops. They feed samples and raw materials were then analyzed in terms of DM (Dry matter), CP (crude protein), EE (ether extract), ash and calcium concentration. Crude protein is the main constituent and is found in the range of 20-22.5% and 15.3-19.5% for broiler and layer feeds, respectively. Moisture content ranged between 9.7-11.2% in both broiler and layer feed indicating good storage condition. Other nutrients such as crude fat and crude fiber content in broiler and layer feed were 3.6-6.9% and 3.0-5.8%, respectively. Layer feed contains a higher amount of calcium (3.1-4.6%) and total ash (8.3-13.3%) than the broiler feed. The moisture percentage of raw materials was below the recommended value. About 40-60% crude protein was found in protein-rich feed ingredients and other nutrients such as crude fat (17.2-19.1%) and crude fiber (9.9-13.1%) were higher in energy-rich ingredients. On the other hand, fungal contamination in broiler and layer feed, and raw materials was found in about 28.5%, 30.0% and 46.0%, respectively. The proximate composition and fungal contamination of poultry feed and raw materials were varied due to environment, processing method, storage condition and adulteration, etc. In conclusion, findings of the nutrient content and fungal contamination of commercial poultry feed and raw materials will help the feed mill owners and commercial poultry farmers to prepare quality feed and to formulate quality poultry ration.